Reactive oxygen species induce injury of the intestinal epithelium during hyperoxia - Zhao, Min (Int J Mol Med, 2018)
Long-term therapeutic hyperoxia may exert serious toxic effects on intestinal epithelial cells in vitro and in vivo. The aim of the present study was to investigate the cause of this intestinal injury under conditions of hyperoxia. Caco-2 cells were treated with different concentrations of hydrogen peroxide (H(2)O(2)) and 85% hyperoxia for 24 h. Higher rates of injury of Caco-2 cells were observed in the hyperoxia and H(2)O(2) groups compared with the control group. The reactive oxygen species (ROS) level of the hyperoxia group was significantly higher compared with that of the 400 μM H(2)O(2) group. The protein and gene levels of RelA, RelB, hypoxia-inducible factor-1α, tumor necrosis factor-α and apoptosis signal-regulating kinase 1 were significantly higher in the hyperoxia and H(2)O(2) groups compared with those in the control group. In conclusion, during hyperoxia, intestinal epithelial cells were destroyed and the levels of ROS were increased. Therefore, ROS may play an important role in intestinal injury in a hyperoxic environment.